2006
DOI: 10.1080/00365540600617009
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-2 infection in injection drug users in King County, Washington

Abstract: Human T-cell lymphotropic virus type 2 (HTLV-2) is endemic in injection drug users (IDU), and native American populations in the Americas. Transmission is associated with high-risk injection and sexual practices. A cohort of 2561 IDU in King County, Washington completed 2 study visits over 1 y. HTLV-2 infection was detected in 190 (7.4%) of 2561 IDU, and 13 (7.8 cases per 1000 person-y) incident infections occurred during the study. Prevalent infection was associated with female gender, non-white race, longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…For many years, tattoos have been considered a risk factor for getting a hepatitis B infection [37,38] and, therefore, we included a question related to hepatitis B in our survey. One percent of the participants were aware of a positive hepatitis B test that had been performed prior to tattooing, and 1% of a test after tattooing.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, tattoos have been considered a risk factor for getting a hepatitis B infection [37,38] and, therefore, we included a question related to hepatitis B in our survey. One percent of the participants were aware of a positive hepatitis B test that had been performed prior to tattooing, and 1% of a test after tattooing.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States and Europe, needle sharing is a major route of HTLV-2 transmission among the PWID population [11][12][13] . Moreover, study of a cohort of PWID in the United States revealed significant associations between HTLV-2 infection and increased rates of pneumonia, acute bronchitis, urinary tract infection, and myelopathy [14] , and the authors noted that the observed high correlation of HTLV-2 infection with HCV infection was suggestive of injection practices as a major route of transmission.…”
Section: Infection Burdenmentioning
confidence: 99%
“…Studies of retroviral transmission carried out in various developing countries have identified incarceration as a risk factor, especially for HCV, suggesting that incarceration may be a surrogate marker for risky behaviour in general, such as needle sharing and unprotected sex [14] . In addition, our previous case report of HTLV in Eastern European countries indicated that the criminalization of drug use and lack of harm reduction strategies in prisons may also serve to increase risk for sexual and parental transmission [15] .…”
Section: Infection Burdenmentioning
confidence: 99%
“…2,17 In Brazil and elsewhere, HCV infection is also common in HTLV-1- and 2-infected individuals, principally among IDUs. 1820 The influence of HTLV-1 and -2 on HCV infection or HIV/HCV coinfection is not well studied, and its pathogenesis is not well understood. In one study among IDUs, HCV viral load was increased in HIV/HTLV-2-infected patients compared with HCV-monoinfected patients.…”
Section: Introductionmentioning
confidence: 99%